2013
DOI: 10.1080/01635581.2013.815233
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genotoxicity and Antigenotoxicity of Artepillin C in V79 Cells by the Comet and Micronucleus Assays

Abstract: Artepillin C (3,5-diprenyl-p-coumaric acid) is one of the major phenolic compounds found in Brazilian green propolis, as well as in its botanical source, Baccharis dracunculifolia DC (Asteraceae). The present study evaluated the possible genotoxic and protective activities of artepillin C, in vitro, using methyl methanesulfonate (MMS) as a positive control, by comet and micronucleus assays. The cultures of Chinese hamster lung fibroblasts (V79 cells) were treated with different concentrations of artepillin C (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Cultures of Chinese hamster lung fibroblasts (V79 cells) were treated with different concentrations of artepillin C (2.5 μM, 5.0 μM, 10.0 μM, and 20 μM) and combined with MMS (comet assay; 200 μM, and micronucleus assay; 400 μM). The study confirmed that all concentrations of artepillin C showed protective activity in relation to MMS-induced genotoxicity; a phenomenon that can be attributed to its antioxidant properties [201].…”
Section: Natural Resinmentioning
confidence: 57%
See 2 more Smart Citations
“…Cultures of Chinese hamster lung fibroblasts (V79 cells) were treated with different concentrations of artepillin C (2.5 μM, 5.0 μM, 10.0 μM, and 20 μM) and combined with MMS (comet assay; 200 μM, and micronucleus assay; 400 μM). The study confirmed that all concentrations of artepillin C showed protective activity in relation to MMS-induced genotoxicity; a phenomenon that can be attributed to its antioxidant properties [201].…”
Section: Natural Resinmentioning
confidence: 57%
“…With these results, baccharin can be considered a chemopreventive agent, whose possible antioxidant effect was responsible for reducing the genomic and chromosomal damages. Likewise, this chemical compound was also responsible for the antigenotoxicity also demonstrated by Baccharis dracunculifolia ; the most important plant source of Brazilian green propolis [201,202,203].…”
Section: Natural Resinmentioning
confidence: 99%
See 1 more Smart Citation
“…• Ação antidiabética e sensibilizadores de insulina (CHOI et al, 2011, IKEDA et al, 2011UEDA et al, 2013) • Oncológica (KIMOTO et al, 2000;KIMOTO et al, 2001a, KIMOTO et al, 2001bAKAO et al, 2003, SHIMIZU et al, 2005SHIMIZU et al, 2006;CHEN et al, 2009aCHEN et al, , 2009bMESSERLI et al, 2009;VOELKEL-JOHNSON, 2011;SZLIS-ZAKA et al, 2011b;FRANCHI et al, 2012;ISHIKAWA et al, 2012;SZLISZKA et al, 2012;DE OLIVEIRA 2013;KIM et al, 2014;MUNARI et al, 2014;FRIÓN-HERRERA et al, 2015, MORTAZAVI et al, 2015, YANG et al, 2017, YOON et al, 2017SOUZA et al, 2018) e…”
Section: Baccharis Dracunculifoliamentioning
confidence: 99%
“…Genotoxicity could occur indirectly by hepatic metabolism of everything that is ingested or inhaled daily. In the last five years, there have been 15.000 published studies investigating antimutagenic and anticarcinogenic substances, with the majority coming from plants. The CA is used to detect genomic alterations.…”
Section: Introductionmentioning
confidence: 99%